2006
DOI: 10.1099/vir.0.81662-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human coronavirus 229E spike and nucleoprotein genes demonstrates genetic drift between chronologically distinct strains

Abstract: Historically, coronaviruses have been recognized as a cause of minor respiratory infections in humans. However, the recent identification of three novel human coronaviruses, one causing severe acute respiratory syndrome (SARS), has prompted further examination of these viruses. Previous studies of geographically and chronologically distinct Human coronavirus 229E (HCoV-229E) isolates have found only limited variation within S gene nucleotide sequences. In contrast, analysis of the S genes of contemporary Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 24 publications
8
64
0
1
Order By: Relevance
“…Only one study has described the variability of the S and N genes over time, which suggests that genetic drift shapes HCoV-229E evolution. 33 Fortunately, the sequence information allows calculation of the evolution rate of the virus. With this evolutionary rate, the time to the most common recent ancestor of HCoV-NL63 and HCoV-229E could be calculated.…”
Section: Evolution and Variability Of Hcov-229e And Hcov-nl63mentioning
confidence: 99%
“…Only one study has described the variability of the S and N genes over time, which suggests that genetic drift shapes HCoV-229E evolution. 33 Fortunately, the sequence information allows calculation of the evolution rate of the virus. With this evolutionary rate, the time to the most common recent ancestor of HCoV-NL63 and HCoV-229E could be calculated.…”
Section: Evolution and Variability Of Hcov-229e And Hcov-nl63mentioning
confidence: 99%
“…The alphacoronavirus, HCoV-229E, is particularly valuable as it circulates in the human population and a sequence database of natural variants isolated over the past fifty years is available. Moreover, changes in sequence and serology have suggested that HCoV-229E is changing over time in the human population [36][37][38] .…”
mentioning
confidence: 99%
“…We then extracted RNAs from the viral fluid, amplified them with HCoV-specific primers, and performed sequence analysis as reported previously (5). We also used the primers COR229ENUC-R2F and COR229ENUC-R1R for sequence analysis (9). We finally confirmed that all these 5 strains contained HCoV-229E genomes.…”
mentioning
confidence: 63%